(Table 1) Age control for magnetic reversals in ODP Hole 138-853B - Wout Krijgsman; Frederik J Hilgen; Isabella Raffi; Francisco Javier Sierro; Douglas S Wilson (PANGAEA, 1999)
The Messinian salinity crisis is widely regarded as one of the most dramatic episodes of oceanic change of the past 20 or so million years (Hsü et al., 1973, doi:10.1038/242240a0; Ryan et al., 1973, doi:10.2973/dsdp.proc.13.1973; Hilgen et al., 1995, doi:10.1016/0012-821X(95)00207-S). Earliest explanations were that extremely thick evaporites were deposited in a deep and desiccated Mediterranean basin that had been repeatedly isolated from the Atlantic Ocean (Ryan et al., 1973, doi:10.2973/dsdp.proc.13.1973; Hilgen et al., 1995, doi:10.1016/0012-821X(95)00207-S), but elucidation of the causes of the isolation - whether driven largely by glacio-eustatic or tectonic processes - have been hampered by the absence of an accurate time frame. Here we present an astronomically calibrated chronology for the Mediterranean Messinian age based on an integrated high-resolution stratigraphy and extquotesingletuning extquotesingle of sedimentary cycle patterns to variations in the Earth extquotesingles orbital parameters. We show that the onset of the Messinian salinity crisis is synchronous over the entire Mediterranean basin, dated at 5.96 +/- 0.02 million years ago. Isolation from the Atlantic Ocean was established between 5.59 and 5.33 million years ago, causing a large fall in Mediterranean water level followed by erosion (5.59-5.50 million years ago) and deposition (5.50–5.33 million years ago) of non-marine sediments in a large extquotesingleLago Mare extquotesingle (Lake Sea) basin. Cyclic evaporite deposition is almost entirely related to circum-Mediterranean climate changes driven by changes in the Earth extquotesingles precession, and not to obliquity-induced glacio-eustatic sea-level changes. We argue in favour of a dominantly tectonic origin for the Messinian salinity crisis, although its exact timing may well have been controlled by the ~400-kyr component of the Earth extquotesingles eccentricity cycle.
Supplement to: Krijgsman, W et al. (1999): Chronology, causes and progression of the Messinian salinity crisis. Nature, 400(6745), 652-655, https://doi.org/10.1038/23231